Seroprevalence of SARS-CoV-2 infection in the Colombo Municipality region, Sri Lanka - Jeewandara, C; Guruge, D; Abyrathna, IS; Danasekara, S; Gunasekera, B; Pushpakumara, PD; Madhusanka, D; Jayathilaka, D; Ranasinghe, T; Somathilake, G; Tanussiya, S; Jayadas, TT; et al. (Frontiers Media, 2021)
Background: As the Municipality Council area in Colombo (CMC) experienced the highest number of cases until the end of January 2021, in Sri Lanka, we carried out a serosurvey prior to initiation of the vaccination program to understand the extent of the SARS-CoV-2 outbreak.